Translation Policy for Linguistic Minorities: a Reception Study Based on Provincial TV in Iran - Jazini, Alireza (Université d'Ottawa / University of Ottawa, 2022)
At the author’s request, the abstract has been removed due to the confidential nature of the thesis. It will be added once the embargo period has passed.
Keywords: Translation Policy; Translation Beliefs; Translation Management; Translation Practice; Translation Reception; Linguistic Minorities